Principles of strategic communication - Holtzhausen, Derina Rhoda; Fullerton, Jami A. 1963-; Lewis, Bobbi Kay 1970-; Shipka, Danny 1967-
"Designed to support the paradigm shift in media and communication, this book presents the basic tenants of strategic communication and its foundational disciplines of advertising, public relations, and marketing communications. Drawing on the latest research in the field, the text introduces students to the theories of strategic communication while at the same time outlining how to apply them to everyday practice. To facilitate learning and tie concepts to practice, each chapter includes introductory focus questions, a contemporary global case study, a career profile of a current practitioner, end-of-chapter discussion questions, and features that highlight how research methods can be applied to strategic communication practice. Principles of Strategic Communication is ideal as a core text for undergraduate students in strategic communication courses within media, communication, marketing, and advertising programs. The accompanying online resources feature chapter summaries, useful links to examples of strategic communication in action, suggested further reading, and practice test questions. Instructors will find an instructor's resource manual that includes sample syllabi, class activities, lecture topics, and a test bank"--Provided by publisher.